Optimizing a protocol for salinity recovery during seedling stage in rice - Siddique, Md. Abubakar; Egdane, James; Bagunu, Efren; Quick, William Paul; Diaz, Maria Genaleen Q.; Henry, Amelia (Informa UK Limited, 2025)
Salinity is one of the major abiotic stresses affecting rice production, but the levels of salinity in a given field are not constant across the growing season. Since the level of salinity in a rice field can fluctuate, fast recovery from salinity stress may be a useful trait to improve rice productivity in salinity-prone areas. To develop a protocol to screen for salinity recovery, seedling stage hydroponic experiments were conducted to measure salinity recovery over time through both destructive and high-throughput image-based phenotyping. Seven rice varieties were included that had previously been classified as tolerant or susceptible to salinity. Following exposure to seedling stage salinity, plants were transferred to solution with no added salt and allowed to recover. Green leaf area and relative growth rates (RGR) of salinity tolerant varieties and one salinity sensitive variety initiated recovery (i.e. started to increase) after 4 days of salt stress removal and required 6 days to completely recover (i.e. to resume a similar RGR to that observed in the no-salt control treatment), while the other salinity sensitive varieties took more time to recover. An optimal recovery period of 6 days after salt stress removal was identified for screening. Based on RGR and chlorophyll fluorescence values, some salinity sensitive varieties recovered while their Na+ contents remained high. Therefore, salinity tolerance may not necessarily correspond to salinity recovery ability. The protocol optimized here can be scaled up to screen diversity panels and populations and used for genetic mapping of the seedling stage salinity recovery trait.